Excess generation and activation of naturally arising memory-phenotype CD4+ T lymphocytes are inhibited by regulatory T cells in steady state - Li, Jing; Yang, Ziying; Kawajiri, Akihisa; Sato, Kosuke; Tayama, Shunichi; Ishii, Naoto; Zhu, Jinfang; Kawabe, Takeshi (Frontiers in Immunology, 2024)
Conventional CD4+ T lymphocytes consist of naïve, foreign antigen-specific memory, and self antigen-driven memory-phenotype (MP) cell compartments at homeostasis. We recently showed that MP cells tonically proliferate in response to self antigens and differentiate into the T-bet+ subset in steady state. How excess proliferation and differentiation of MP cells are inhibited remains unclear. Given immunosuppressive function of regulatory T cells (Tregs), it is possible that they are also involved in inhibition of spontaneous MP cell activation. Here we show using Foxp3-diphtheria toxin receptor-transgenic mice that both MP and naïve CD4+ T cells spontaneously proliferate and differentiate into Th1 cells upon acute Treg depletion. At an early time point post Treg depletion, MP as compared to naïve CD4+ T cells are preferentially activated while at a later stage, the response is dominated by activated cells originated from the naïve pool. Moreover, we argue that MP cell proliferation is driven by TCR and CD28 signaling whereas Th1 differentiation mediated by IL-2. Furthermore, our data indicate that such activation of MP and naïve CD4+ T lymphocytes contribute to development of multi-organ inflammation at early and later time points, respectively, after Treg ablation. Together our findings reveal that Tregs tonically inhibit early, spontaneous proliferation and Th1 differentiation of MP CD4+ T lymphocytes as well as late activation of naïve cells, thereby contributing to maintenance of T cell homeostasis.